Chinese Religions Going Global - Cao, Nanlai,; Yang, Fenggang,; Giordan, Giuseppe, (Annual Review of the Sociology of Religion ;, 2021)
"As China is being increasingly integrated into the global economy, more and more Chinese people live transnational lives and practice religion globally. So far scholarship of the relationship between religion and globalization in the Chinese religious field has primarily been set in the historical context of the encounter between Western Christian missionaries and local Chinese agents, and little is known about a global Chinese religious field that is in the making. The Annual Review of the Sociology of Religion volume 11: Chinese Religions Going Global seeks to challenge the dichotomous ordering of the western global and the Chinese local, and to add a new perspective for understanding religious modernity globally. Contributors from four continents who represent a range of specialisms apply social scientific methods in order to systematically research the globalization of Chinese religions. Contributors are Jacqueline Armijo, Fabio Berti, Nikolas Broy, Nanlai Cao, Shaojin Chai, Marco Guglielmi, Jie Kang, Thoralf Klein, Xinan Li, Jifeng Liu, Line Nyhagen, Utiraruto Otheode, Valentina Pedone, Benjamin Penny, Anna Sun, Jonathan Tam, Grazia Ting Deng, Yuting Wang, Chris White, Hung-Jen Yang"--